Oncolytic reovirus combined with trastuzumab enhances antitumor efficacy through TRAIL signaling in human HER2-positive gastric cancer cells. Issue 2 (28th January 2015) - Hamano, Shingo; Mori, Yoshinori; Aoyama, Mineyoshi; Kataoka, Hiromi; Tanaka, Mamoru; Ebi, Masahide; Kubota, Eiji; Mizoshita, Tsutomu; Tanida, Satoshi; Johnston, Randal N.; Asai, Kiyofumi; Joh, Takashi
Highlights: Trastuzumab is effective for HER2-overexpressing gastric cancer therapy. Oncolytic reovirus is currently undergoing clinical trials internationally. Reovirus combined with trastuzumab enhances antitumor efficacy in vitro and in vivo . Combination therapy induces higher TRAIL expression in cancer cells. Reovirus may augment trastuzumab-induced cytotoxicity in cancer cells. Abstract: The human epidermal growth factor receptor 2 (HER2)-targeting agent, trastuzumab, is effective for HER2-overexpressing gastric cancer therapy. As oncolytic reovirus is currently undergoing clinical trials internationally, we wanted to explore whether combination therapy using trastuzumab and reovirus might provide a novel, more effective therapeutic option for gastric cancer. Cell proliferation and cell apoptosis were examined in vitro, while molecular analysis of pathways responsible for cell damage was examined using polymerase chain reaction array. Activation of the proteins related to apoptosis, cell growth and survival was detected by Western blotting. Mouse tumor xenograft models were used to examine antitumor activity in vivo . Reovirus sensitized HER2-overexpressing gastric cancer cells to undergo apoptosis. Both in vitro and in vivo studies provided evidence that the combination therapy is a more powerful modality against HER2-overexpressing gastric cancer cells than treatment using a single agent. Molecular analysis indicated that combination therapy induced significantly higher levels of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) in cancer cells. Antibody against TRAIL strongly inhibited cell toxicity caused by the combined treatment. These data suggest that reovirus may augment trastuzumab-induced cytotoxicity in gastric cancer cells.